Vai trò của kế toán quản trị trong việc thúc đẩy học tập tổ chức, năng lực đổi mới và kết quả hoạt động kinh doanh ở các doanh nghiệp tại Việt Nam - Tran Thi, Yen; Nguyen Phong , Nguyen (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
Drawing upon the resource-based view (RBV), the knowledge-based view (BKV) and the contingency theory, this study aims to examine the moderating role of the use of management accounting systems on the relationship between firms’ organizational learning and innovation capability. In addition, this study tests the mediating effect of innovation capability on the relationship between organizational learning and firm performance of Vietnamese firms. Survey data was collected from a sample of 288 middle- and high-level managers in large firms in Vietnam. The PLS-SEM testing results show that: (i) The extent of the use of the management accounting systems (including four dimension such as broad scope timeliness, aggregation, and integration) moderates the relationship between organizational learning and innovation capability; and (ii) innovation capability and the using level of management accounting systems both have significant positive effectson firm performance. The research results provide theoretical and managerial implications to Vietnamese firms to maximize the use of managerial accounting systems towards enhancing innovation capability and organizational performance.